2017
DOI: 10.1007/s00204-017-2102-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel, integrated in vitro carcinogenicity test to identify genotoxic and non-genotoxic carcinogens using human lymphoblastoid cells

Abstract: Human exposure to carcinogens occurs via a plethora of environmental sources, with 70–90% of cancers caused by extrinsic factors. Aberrant phenotypes induced by such carcinogenic agents may provide universal biomarkers for cancer causation. Both current in vitro genotoxicity tests and the animal-testing paradigm in human cancer risk assessment fail to accurately represent and predict whether a chemical causes human carcinogenesis. The study aimed to establish whether the integrated analysis of multiple cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 70 publications
2
28
0
Order By: Relevance
“…The parallel assessment of multiple, holistic endpoints may enable a broad range of carcinogenic mechanisms to be monitored and link to adverse outcome pathways (AOPs) (Burden et al 2015 ). Previously, we have demonstrated that integrated in vitro endpoints show promise in distinguishing genotoxic carcinogens from non-genotoxic carcinogens, with results also correlating well with in vivo data (Wilde et al 2018 ).…”
Section: Introductionsupporting
confidence: 74%
See 4 more Smart Citations
“…The parallel assessment of multiple, holistic endpoints may enable a broad range of carcinogenic mechanisms to be monitored and link to adverse outcome pathways (AOPs) (Burden et al 2015 ). Previously, we have demonstrated that integrated in vitro endpoints show promise in distinguishing genotoxic carcinogens from non-genotoxic carcinogens, with results also correlating well with in vivo data (Wilde et al 2018 ).…”
Section: Introductionsupporting
confidence: 74%
“…While there was some overlap between toxic non-carcinogens and misleading positives, toxic non-carcinogens generally ranked higher with an average ISC of 22.3, compared to 15.7 for misleading positives. There did appear to be some overlap between non-carcinogen ISCs and non-genotoxic carcinogens ISCs published previously by Wilde et al (2018); non-carcinogen cycloheximide's ISC was 28.4, whereas non-genotoxic carcinogens NiCl 2 and DEHP produced lower ISCs of 27.1 and 26.4, respectively. As previously mentioned, it is, however, possible that cycloheximide is inherently genotoxic (Fig.…”
Section: Isc Scores Successfully Distinguished Carcinogens From Non-cmentioning
confidence: 54%
See 3 more Smart Citations